Horizon of Expectation of Childrenâ€™s Ideal Future in 1946 Represented in Enid Blytonâ€™s 'Malory Towers' (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
1946 was a recovery year after Second World War ended and the early modern era. At the beginning of modern era, children were taught the basic attitude of well manners and respecting others. The social attitudes into children give adults more attention to children as separate beings, innocent, and need of protection. Therefore, this study aimed to explain (1) what British expectation toward childrenâ€™s future described on Enid Blytonâ€™s Malory Towers (2) childrenâ€™s characters in Enid Blytonâ€™s Malory Towers formed by the participation of British role and (3) todayâ€™s perspective of British ideas in 1946. Qualitative descriptive study is employed with â€œhorizon of Expectationâ€ of reader response theory by Hans Robert Jauss is served to analyze the data. It is found that as illustrated in Malory Towers, British were expected their children to be kind, good-hearted, loved, trusted, and reliable child. In addition, parents, school, and friendâ€™s role are important to forming childrenâ€™s character to teach some values such as discipline, responsible, politeness, caring, loyal and understanding, respectful, mental strength, steady and wise attitude to reach the ideal future. On other hand, in 1946, education aims to change the society to fit the ideas of the ruling government or to create the utopian society through education. Furthermore, there are some similarities and differences of British ideas in 1946 and todayâ€™s perspective of British education system and boarding school in which all the ideas have a good aim for childrenâ€™s future.s